2023
DOI: 10.3389/fimmu.2023.1267816
|View full text |Cite
|
Sign up to set email alerts
|

13C tracer analysis reveals the landscape of metabolic checkpoints in human CD8+ T cell differentiation and exhaustion

Alexander Kirchmair,
Niloofar Nemati,
Giorgia Lamberti
et al.

Abstract: IntroductionNaïve T cells remain in an actively maintained state of quiescence until activation by antigenic signals, upon which they start to proliferate and generate effector cells to initiate a functional immune response. Metabolic reprogramming is essential to meet the biosynthetic demands of the differentiation process, and failure to do so can promote the development of hypofunctional exhausted T cells.MethodsHere we used 13C metabolomics and transcriptomics to study the metabolism of CD8+ T cells in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…One indicator of the activation of CD8 + T cells is the transition from OXPHOS to aerobic glycolysis, and the mTORC1-HIF-1 pathway is critical for mediating this metabolic transition ( Finlay et al, 2012 ; Kirchmair et al, 2023 ). The expression of glycolytic proteins and the rate of glycolysis were greater in differentiated CD8 + effector T cells than in naïve T cells.…”
Section: What About Glycolysis Reprogramming In the Tme?mentioning
confidence: 99%
See 1 more Smart Citation
“…One indicator of the activation of CD8 + T cells is the transition from OXPHOS to aerobic glycolysis, and the mTORC1-HIF-1 pathway is critical for mediating this metabolic transition ( Finlay et al, 2012 ; Kirchmair et al, 2023 ). The expression of glycolytic proteins and the rate of glycolysis were greater in differentiated CD8 + effector T cells than in naïve T cells.…”
Section: What About Glycolysis Reprogramming In the Tme?mentioning
confidence: 99%
“…Glycolysis not only promotes tumor growth but also modifies the TME by impacting immune cell and stromal cell development, activation, and function. Nonmalignant cells, such as immune cells ( Kirchmair et al, 2023 ) and cancer-associated fibroblasts ( Yan et al, 2018 ), undergo metabolic reprogramming during carcinogenesis that is notable for its increased dependence on glycolysis. Additionally, by promoting the production of metabolites and signaling chemicals, glycolysis of tumor cells can positively alter the TME ( Guo et al, 2022 ; Liu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent tracer studies have shown that the carbon atoms provided by fed glucose appear in lactate (also produced by the heart muscle) and in other downstream metabolites. In turn, lactate is also routinely utilized by virtually all tissues to feed the TCA cycle and other pathways [28,[64][65][66][67][68][69][70] (see Figure 1). Moreover, lactate can even stimulate its own use by mitochondria by yet unknown mechanisms, independent of its actual use [69].…”
Section: Glucose and Lactate Metabolism In Normal Body Tissuesmentioning
confidence: 99%